2022
DOI: 10.1371/journal.pone.0269586
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem-based adaptation for increased agricultural productivity by smallholder farmers in Nepal

Abstract: The impacts of climate change are evident in the agriculture sector globally. These impacts are more severe and pronounced in a mountainous country like Nepal due to the high reliance on agro-economy and subsistence-based livelihoods by smallholder farmers that increase vulnerability and risks. Several ecosystem-based adaptation measures have proved to build the adaptive capacity of both agro-ecosystems and smallholder farmers by offering simple and affordable technologies however, these are yet to be prioriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The plants used are usually fast decomposing with insect-repellent properties. The Jholmal is to be used in 1.2 liters per m2(Bhusal et al, 2022), and the effective frequency of use was observed to be 21 days(Acharya et al, 2020). The Jholmal was prepared on the farm using locally available plants (Artemisia vulgaris, Melia azedarach, Allium sativum, Urtica dioica, Zanthoxylum piperitum, Trifolium, Portulaca oleracea ), cattle urine, and effective microorganisms (EM) bought from the market.…”
mentioning
confidence: 99%
“…The plants used are usually fast decomposing with insect-repellent properties. The Jholmal is to be used in 1.2 liters per m2(Bhusal et al, 2022), and the effective frequency of use was observed to be 21 days(Acharya et al, 2020). The Jholmal was prepared on the farm using locally available plants (Artemisia vulgaris, Melia azedarach, Allium sativum, Urtica dioica, Zanthoxylum piperitum, Trifolium, Portulaca oleracea ), cattle urine, and effective microorganisms (EM) bought from the market.…”
mentioning
confidence: 99%